Effective Teacher Professional Development for School-Based Mental Health Promotion: A Review of the Literature - Hannah L. Dinnen; Nicole S. Litvitskiy; Paul D. Flaspohler (Behavioral Sciences)
Teachers are critically involved in the delivery of school-based mental health promotion (SMHP) interventions in school, though pre-service teacher education often leaves teachers feeling underprepared in this area. Thus, understanding how best to build teachers’ capacity for delivery through effective professional development (PD) is essential for teachers to fulfill their role as delivery agents to achieve SMHP outcomes. This systematized review focuses on identifying components of high-quality teacher PD for SMHP and examining the empirical support for these components. In a two-phase analysis, we examined the descriptive literature regarding teacher PD for SMHP to identify common elements. This resulted in the identification of components relevant to training (interactive, guided by staff input) and technical assistance (TA), including the goals (skill development, motivation, generalization/adaptation), approach (collaborative, individualized, data-driven, strengths-based), and activities (modeling, performance feedback, reflection, problem solving) involved. A second phase focused on the examination of empirical evidence for these PD components. While the empirical evidence for these components was limited, the identified components represent a current standard of practice in teacher PD for SMHP, based on the existing research. These components may provide a framework for practical use in planning teacher PD related to SMHP and for designing future research into effective capacity building in this area.